2016
DOI: 10.1037/pac0000185
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the macrosystem in postaccord Northern Ireland: A social–ecological approach.

Abstract: is a PhD student in developmental psychology and peace studies at the University of Notre Dame. Her research interests focus on the impact of political and community violence on youth development through the Kroc Institute for International Peace Studies and the Department of Psychology.LAURA K. TAYLOR holds a PhD. She is an assistant professor at the Centre for Identity and Intergroup Relations in the School of Behavioural Sciences at Queen's University Belfast. Her research focuses on risk and resilience pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The form and content of news, when aggregated over time, can shape and inform individual responses to the conflict. As a result, local news sources can be a useful resource for assessing the overarching political climate surrounding a conflict (Myers & Caniglia, 2004;Townsend et al, 2016). Many studies have used coded news reports to research sociopolitical phenomena (e.g., Barclay & Liu, 2003;Coleman & Wasike, 2004;Heber, 2011;Kim, Kumanyika, Shive, Igweatu, & Kim, 2010;Miller, Peake, & Boulton, 2010;Perkins & Taylor, 1996;Trenz, 2004), but few have tested the psychological impact of these sociopolitical events.…”
Section: Measurement Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The form and content of news, when aggregated over time, can shape and inform individual responses to the conflict. As a result, local news sources can be a useful resource for assessing the overarching political climate surrounding a conflict (Myers & Caniglia, 2004;Townsend et al, 2016). Many studies have used coded news reports to research sociopolitical phenomena (e.g., Barclay & Liu, 2003;Coleman & Wasike, 2004;Heber, 2011;Kim, Kumanyika, Shive, Igweatu, & Kim, 2010;Miller, Peake, & Boulton, 2010;Perkins & Taylor, 1996;Trenz, 2004), but few have tested the psychological impact of these sociopolitical events.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…Accordingly, the research team developed the plan to use newspaper coding as a macrosystem measure. A prior study by Townsend et al (2016) demonstrated that political tension between groups—when measured by coded news reports—provided information about the social ecology that was missed by other measures. The current monograph builds on this methodology to assess how both political tension and ingroup threat in the macrosystem relate with the proximal processes that have already been found to increase adolescents’ emotional insecurity and subsequent adjustment problems.…”
Section: History Of the Projectmentioning
confidence: 99%
“…As another example, when antisocial behavior precedes exposure to political violence, a key feature could be accounted for by increased involvement in deviant peer associations. As further example, elements of the macro-system (e.g., political discord between Catholics and Protestants) may possibly contribute to both variables (Townsend et al, 2016). Finally, although notions of causal relations between "adolescent adjustment effects" and "sectarian community violence effects" cannot be tested in the current study, the directionality over time can be assessed within the longitudinal design.…”
Section: Discussionmentioning
confidence: 99%
“…For example, social identity may function differently for both Catholics (historic minority) and Protestants (historic majority) in the post-accord era (Merrilees et al, 2011, 2014). Finally, in line with the DPM (Taylor, 2020), the article focuses on broader support for the peace process at the macrosystem level (Townsend et al, 2016).…”
Section: Current Studymentioning
confidence: 99%